1988
DOI: 10.1021/ie00082a023
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporation of methanol-ethylene glycol with cellophane membrane: some mechanistic aspects

Abstract: The relationship between two-phase and three-phase solutions to heterogeneous distillation simulation and optimization problems is studied. Simulation results illustrate that bifurcation points can occur in the two-phase solutions and that, in regions of steady-state two-phase solution multiplicity, not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…It is worth mentioning that, compared to cellophane membrane used for methanol/ethylene glycol separation, higher methanol selectivity with almost similar fluxes are achieved by the PPO membranes prepared for this study [6], while in comparison to the copolymerized acrylonitrile membranes with hydroxyethyl methacrylate, methacrylic acid or vinyl pyrrolidone, both flux and methanol selectivity obtained by PPO membranes are higher [7].…”
Section: Membrane Watermentioning
confidence: 59%
See 3 more Smart Citations
“…It is worth mentioning that, compared to cellophane membrane used for methanol/ethylene glycol separation, higher methanol selectivity with almost similar fluxes are achieved by the PPO membranes prepared for this study [6], while in comparison to the copolymerized acrylonitrile membranes with hydroxyethyl methacrylate, methacrylic acid or vinyl pyrrolidone, both flux and methanol selectivity obtained by PPO membranes are higher [7].…”
Section: Membrane Watermentioning
confidence: 59%
“…In fact, the diffusion cross section of methanol, 14.4 Å 2 , is lower than that of ethylene glycol, 23.4 Å 2 [7]. For pervaporation of methanol-ethylene glycol mixture, Ghosh et al [6] and Ray et al [7] obtained similar trends when using cellophane and copolymerized acrylonitrile membranes, respectively.…”
Section: Membrane Watermentioning
confidence: 89%
See 2 more Smart Citations
“…Later, Mulder et al (1982) applied pervaporation to the separation of isomeric xylenes by thin films of cellulose esters. Recently, Ghosh et al (1988) reported separating mixtures of methanol and ethylene glycol by cellophane membranes.…”
Section: Introductionmentioning
confidence: 99%